Enhancing Creative Skills in Fashion and Textile Students through National Embroidery Workshops” - Nematova Tursuntosh Alisher qizi (O‘RTA OSIYODA IJTIMOIY VA GUMANITAR TADQIQOTLAR, 2025)
Abstract: This article explores how national embroidery workshops can enhance creative skills in fashion and textile students. Integrating traditional embroidery techniques into educational workshops allows students to develop artistic competencies, innovative thinking, and cultural awareness. The study examines pedagogical strategies, project implementation, and the impact of hands-on embroidery training on students’ creative and professional development. Research findings indicate that these workshops effectively nurture creativity, aesthetic appreciation, and technical proficiency among students.